An Update on Sec61 Channel Functions, Mechanisms, and Related Diseases - Lang, Sven; Pfeffer, Stefan; Lee, Po-Hsien; Cavalié, Adolfo; Helms, Volkhard; Förster, Friedrich; Zimmermann, Richard (Frontiers in Physiology, 2017)
The membrane of the endoplasmic reticulum (ER) of nucleated human cells harbors the protein translocon, which facilitates membrane integration or translocation of almost every newly synthesized polypeptide targeted to organelles of the endo- and exocytotic pathway. The translocon comprises the polypeptide-conducting Sec61 channel and several additional proteins and complexes that are permanently or transiently associated with the heterotrimeric Sec61 complex. This ensemble of proteins facilitates ER targeting of precursor polypeptides, modification of precursor polypeptides in transit through the Sec61 complex, and Sec61 channel gating, i.e. dynamic regulation of the pore forming subunit to mediate precursor transport and calcium efflux. Recently, cryoelectron tomography of translocons in native ER membrane vesicles, derived from human cell lines or patient fibroblasts, and even intact cells has given unprecedented insights into the architecture and dynamics of the native translocon and the Sec61 channel. These structural data are discussed in light of different Sec61 channel activities including ribosome receptor function, membrane insertion, and translocation of newly synthesized polypeptides as well as the putative physiological roles of the Sec61 channel as a passive ER calcium leak channel. Furthermore, the structural insights into the Sec61 channel are incorporated into an overview and update on Sec61 channel–related diseases – the Sec61 channelopathies – and novel therapeutic concepts for their treatment.